Efficacy and Safety of Cangfu Daotan Decoction in Patients with Polycystic Ovary Syndrome: A Systematic Review and Meta-Analysis. (17th May 2022) - Wu, Linling; Zhang, Han; Fan, Mengxiao; Yan, Ying
Abstract : Background . The infertility caused by polycystic ovary syndrome (PCOS) has received considerable attention. Considerable efforts have been made to improve the rates of pregnancy and live birth. Cangfu Daotan Decoction (CFDTD) is a classic prescription for treating infertility in obese women. The efficacy of CFDTD in PCOS is controversial. Objective . To evaluate the effectiveness and safety of CFDTD in treating infertility with PCOS. Methods . A literature search was performed in the Cochrane Library, PubMed, Embase, the China National Knowledge Infrastructure, the Wanfang Database, the VIP Chinese Biomedical science journal database, and the Chinese BioMedical database from the date of each database establishment to December 2021. Only randomized controlled trials, which were used to evaluate the efficacy of CFDTD in treating subjects with PCOS, were included in the present study. The quality of evidence was assessed using the Cochrane Reviewer Handbook 5.0.0, and meta-analysis was performed using RevMan 5.3.5 software. Results . Fourteen studies with a total of 1, 433 patients were included in this analysis. The present study indicated that CFDTD could significantly improve pregnancy rate (RR = 1.62, 95% CI (1.44, 1.83), P < 0.00001 ), ovulation rate (RR = 1.40, 95% CI (1.25, 1.56), P < 0.00001 ), and estradiol levels (SMD = 0.80, 95% CI (0.03, 1.58), P = 0.04 ), while testosterone levels (SMD = −0.92, 95% CI (−1.52, −0.31), P = 0.003 ), homeostatic model assessment for insulin resistance (MD = −0.56, 95% CI (−0.99, −0.12), P = 0.01 ), total cholesterol levels (MD = −0.60, 95% CI (−0.76, −0.44), P < 0.00001 ), triglyceride levels (MD = −0.48, 95% CI (−0.60, −0.36), P < 0.00001 ), body mass index (MD = −2.96, 95% CI (−3.88, −2.03), P < 0.00001 ), and the incidence of adverse reactions (RR = 0.47, 95% CI (0.34, 0.65), P < 0.00001 ) were significantly reduced. Conclusions . Evidence from the meta-analysis suggested that CFDTD appeared to be an effective and relatively safe treatment for PCOS. However, the influence of CFDTD on reproductive hormones, glucose metabolism, and blood lipids should be carefully concluded. Due to the low quality of the methods used in the included randomized controlled trials, further studies are required with larger sample sizes and well-designed models to confirm our findings.